2023
DOI: 10.26508/lsa.202301899
|View full text |Cite
|
Sign up to set email alerts
|

The ERK activator, BCI, inhibits ciliogenesis and causes defects in motor behavior, ciliary gating, and cytoskeletal rearrangement

Abstract: MAPK pathways are well-known regulators of the cell cycle, but they have also been found to control ciliary length in a wide variety of organisms and cell types fromCaenorhabditis elegansneurons to mammalian photoreceptors through unknown mechanisms. ERK1/2 is a MAP kinase in human cells that is predominantly phosphorylated by MEK1/2 and dephosphorylated by the phosphatase DUSP6. We have found that the ERK1/2 activator/DUSP6 inhibitor, (E)-2-benzylidene-3-(cyclohexylamino)-2,3-dihydro-1H-inden-1-one (BCI), inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…We also checked the ability for cilia to completely regenerate from zero length through pH shock which involves dropping the cell suspension pH to 4.5 for 45 seconds with 0.5 M acetic acid and returning the pH to 7.0 with 0.5 M KOH (Witman et al, 1972) in the presence of 15 µM PTX (confirmed to stabilize microtubules at this concentration), 40 µM PTX, or 60 µM PTX compared to control cells in DMSO (Figure 1D). Similarly and consistent with our previous work (Dougherty et al, 2023), cilia regenerated normally in 15 µM PTX, though even at 60 µM PTX, ciliary length did not differ from DMSO treated cells at 120m (Figure 1D). To compare the ability for PTX to stabilize microtubules during pH shock, we pretreated cells for 10 min with PTX and before pH shock and then fixed and stained them for beta tubulin within 5 minutes when microtubules are normally depolymerized (Figure 1E).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We also checked the ability for cilia to completely regenerate from zero length through pH shock which involves dropping the cell suspension pH to 4.5 for 45 seconds with 0.5 M acetic acid and returning the pH to 7.0 with 0.5 M KOH (Witman et al, 1972) in the presence of 15 µM PTX (confirmed to stabilize microtubules at this concentration), 40 µM PTX, or 60 µM PTX compared to control cells in DMSO (Figure 1D). Similarly and consistent with our previous work (Dougherty et al, 2023), cilia regenerated normally in 15 µM PTX, though even at 60 µM PTX, ciliary length did not differ from DMSO treated cells at 120m (Figure 1D). To compare the ability for PTX to stabilize microtubules during pH shock, we pretreated cells for 10 min with PTX and before pH shock and then fixed and stained them for beta tubulin within 5 minutes when microtubules are normally depolymerized (Figure 1E).…”
Section: Resultssupporting
confidence: 92%
“…It has previously been shown that 40 µM paclitaxel (PTX), a microtubule stabilizer, inhibits ciliary elongation through lithium chloride and stunts ciliary length when grown from zero length (Wang et al, 2013). However, we found in our previous work that a lower paclitaxel concentration, 15 µM PTX, can allow for normal ciliary elongation following pH shock in Chlamydomonas (Dougherty et al, 2023). In addition, it is well known that higher concentrations of taxol, a paclitaxel equivalent, can induce different processes from lower concentrations, and lower concentrations of taxol can inhibit microtubule dynamics without altering tubulin polymer mass which occurs with higher concentrations (Derry et al, 1998;Jordan et al, 1993).…”
Section: Resultsmentioning
confidence: 66%
“…Based on the literature, one strong candidate was the MAP kinases cascade and ERK in particular since this central pathway has been shown to regulate ciliogenesis [27]. For example, dephosphorylation of ERK by DUSP6 phosphatase reduces cilia length in RPE cells and in Chlamydomonas reinhardtii [27]. Also, cisplatin treated cells kidney tubular epithelial cells have shorter cilia and activated ERK while inhibition of pERK by U0126 during cisplatin treatment elongates cilia [28].…”
Section: Resultsmentioning
confidence: 99%
“…ERK is primarily regulated by MEK1 kinase and by DUSP6 phosphatase. Interestingly, the activation of ERK by a DUSP6 inhibitor reduces cilia length in Chlamydomonas reinhardtii and in hTERT-RPE1 cells [27]. We also tested any effect of FSTL1 depletion on SMAD1/5/8 activation as a mediator of the canonical BMP signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation